Internal Communication Dan Total Quality Management Untuk Meningkatkan Employee Performance Paramedis Puskesmas Barengkrajan, Krian, Sidoarjo - Pitra Bhagas Kara; Amiartuti Kusmaningtyas (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Puskesmas Barengkrajan is a Puskesmas located in the west of Sidoarjo Regency and is located in Barengkrajan Village, Krian District. Puskesmas Barengkrajan as the spearhead of basic health services, continues to strengthen efforts to increase awareness, willingness, and ability to live healthy people in their work areas. Supported by qualified health workers, this puskesmas is ready to serve the community. Even to facilitate and speed up services, the Sidoarjo Regency Health Office has prepared an Auxiliary Health Center in Punokawan village and service assistance activities at posyandu, polindes, poskestren, and Poskesdes. This study aims to determine the influence on Internal Communication and Total Quality Management to Improve the Performance of Employees of Puskesmas Barengkrajan, Krian, Sidoarjo. The number of samples used in this study was 40 paramedics with the saturated sample method. The data analysis technique used is simple linear regression analysis. The results of this study show that internal communication and total quality management variables have an influence on employee performance. With the results obtained, the Internal Communication variable has a significant effect on Total Quality Management. The variable of Total Quality Management affects Employee Performance. Internal Communication variables affect Employee Performance.